A study of landed housing defects in Seri Iskandar, Perak - Md Sa’at, Nur Shuhadah (2024)
Building defects are structural, functional, or aesthetically pleasing defects in a built structure that affect its integrity, safety, or overall performance. Building defects are a common issue in the construction industry, including a wide range of difficulties that risk the structural integrity, safety, and functionality of built facilities. The aim of this research is to study landed housing defects in Seri Iskandar, Perak. The objectives of this research is to identify the type of defects for landed houses in Malaysia, to identify the causes of defects for landed houses, and to recommend the best solution for the defects of landed houses. The data for the study is gathered using a qualitative method. It includes a structured interview and observation where these methods are needed to collect the information to achieve the objectives. The interview was divided into two which are 15 residents from 3 different areas and three professional teams. All the primary data were gathered from the respondents. In conclusion, the results revealed several serious problems including peeling paint, wall and ceiling fractures, and fungal problems, but there were also types of defects that did not occur in the building such as the plumbing, electrical, drainage, and tile installation. The findings of this research may help future studies to search in more detail for the defects or different types of buildings.